Albur, “naquiza”, camp y manierismo en el cabaret de Regina Orozco - Alzate, Gastón A. (Latin American Theatre Review, 2011)
This essay analyses the work of Mexican cabaret artist Regina Orozco, focusing in particular on the incorporation of the operatic tradition in cabaret, the cultural dynamic of Mexican albur and the visual aesthetics of her performances. Her strategic use of the albur is seen as a way to subvert notions of gender and the female body. It is also related to her creative use of popular, regional and academic musical genres (e.g., opera and bel canto). The mixture of elements of so-called high and low culture is discussed in connection with Carlos Monsiváis’s ideas regarding naquiza and lo naco, and also with regard to the artistic origins of mannerism and camp. This article explores several of Orozco’s cabaret shows such as Rosa Mexicano, Regina en el Diván, Regina en Celo sa, Los monólogos de la Regina, Boleros, boleritos y flores para Chava, and her video-performance Tlacoyo con Co-K Light. (GAA, article in Spanish)